Bone morphogenetic protein 4 regulates microRNAs miR-494 and miR-126–5p in control of endothelial cell function in angiogenesis - Esser, Jennifer S.; Saretzki, Erika; Pankratz, Franziska; Engert, Bianca; Grundmann, Sebastian; Bode, Christoph; Moser, Martin; Zhou, Qian (Thrombosis and Haemostasis, 2017)
MicroRNAs are small non-coding RNAs that negatively regulate posttranscriptional gene expression. Several microRNAs have been described to regulate the process of angiogenesis. Previously, we have shown that bone morphogenetic protein 4 (BMP4) increased the proangiogenic activity of endothelial cells. In this project, we now investigated how the pro-angiogenic BMP4 effect is mediated by microRNAs. First, we performed a microRNA array with BMP4-stimulated human umbilical vein endothelial cells (HUVECs). Among the topregulated microRNAs, we detected a decreased expression of miR-494 and increased expression of miR-126–5p. Next, we analysed the canonical Smad and alternative signalling pathways, through which BMP4 would regulate miR-126–5p and miR-494 expression. Furthermore, the functional effect of miR-494 and miR-126–5p on endothelial cells was investigated. MicroRNA-494 overexpression decreased endothelial cell proliferation, migration and sprout formation. Consistently, miR-494 inhibition increased endothelial cell function. As potential miR-494 targets, bFGF and BMP endothelial cell precursorderived regulator (BMPER) were identified and confirmed by western blot. Luciferase assays showed direct miR-494 binding in BMPER 3’UTR. In contrast, miR-126–5p overexpression increased pro-angiogenic endothelial cell behaviour and, accordingly, miR-126–5p inhibition decreased endothelial cell function. As a direct miR-126–5p target we identified the anti-angiogenic thrombospondin-1 which was confirmed by western blot analysis and luciferase assays. In the Matrigel plug assay application of antagomiR-494 increased endothelial cell ingrowth, whereas antagomiR-126–5p treatment decreased cell ingrowth in vivo. Taken together, through differential regulation of the anti-angiomiR-494 and the angiomiR-126–5p by BMP4 both microRNAs contribute to the pro-angiogenic BMP4 effect on endothelial cells.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: BMP4; microRNAs; angiogenesis; endothelial cells